Perancangan Antena Mikrostrip Circular Patch MIMO 2x2 Untuk Aplikasi Wireless Fidelity (WiFi) Pada Frekuensi Kerja 2,4 GHz - Egi Pratama; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The antenna has a big role either in high or low frequency of wireless communication. In transmission process, antenna also become a determinant factor of successful communication between transmitter and receiver. In this project, we will design an omnidirectional antenna that will be connected with electrical unit measurement device. To make analyzing process easier, ansoft hfss 13.0 software will beused. The simulation results show that the antenna canwork well at frequency of 2,4 until 2,5 GHz, return loss -30,4670, gain 5,08 and VSWR 1,0618.Keyword: microstrip antenna, Wi – Fi , return loss, VSWR